TRANSCULWRATION AND PERMANENCE OF MYTH IN DIOSES Y HOMBRES DE HUAROCHIRÍ - Loli Tarazona, Walter (2007)
Chapters 20 and 21 of Gods and Men of Huarochiri show the mythic voice enacting reproachingwords towards Andean tradition and at the same time a respectful acceptanceof preaching coming from the "extirpador" of idolatries. Also, are easily given creditFather Davila · s admonitions about the slow progress of the Word among the natives because they remained "lost" in their "errors, superstitions and satanic rites". However,as it is reported, although we see the end of a huaca in the community of Checas andthe victory over it from a converted Christian, the religious conception of the universeis founded on an Andean dualitry. The old beliefs remain and it is not true that theyhave been vanquished by the Christian god. Myth is the repository of the new "power"conditions.